New records and updated checklist of heterobranch sea slug (Gastropoda: Heterobranchia) from South Malang, Indonesia - ANTHON ANDRIMIDA; LUCHMAN HAKIM; CATUR RETNANINGDYAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Andrimida A, Hakim L, Retnaningdyah C. 2025. New records and updated checklist of heterobranch sea slug (Gastropoda: Heterobranchia) from South Malang, Indonesia. Biodiversitas 26: 3674-3693. This article presents an integrated and updated checklist of heterobranch sea slug species from South Malang, East Java, Indonesia, based on additional records from recent surveys, published records and citizen scientist findings since 2019. A different approach to survey method was conducted during this study, where surveys were done by exploring shallow tidepools in contrast to previous studies in South Malang that followed SCUBA diving-based survey. Twelve surveys have been conducted at three new localities in South Malang from September 2024 to March 2025. A total of 14 new species has been successfully documented as new locality records from three main sites, which are Banyu Towo, Tanjung Penyu, and Gatra. These 14 species assigned to the Aplysiida order (two species), Sacoglossa superorder (three species), Pleurobranchida order (three species) and Nudibranchia order (six species). With this finding, combined with previous studies, a total of 79 heterobranch sea slug species has been recorded from South Malang, which 57 species belong to the Nudibranchia order, nine species belong to the Aplysiid order, eight species belong to the Sacoglossa superorder, three species belong to the Pleurobranchida order, and two species belong to the Cephalaspidea order were found. This study also provides nine species corrections from past studies following taxonomical update or possible misidentification in the past. Compared to other records, it is revealed that heterobranch sea slug species diversity in South Malang is higher than the average heterobranch sea slug species diversity in Java Region. Higher heterobranch sea slug diversity indicates diverse habitat structure and higher overall diversity in coral reef ecosystem. This study provides baseline data for future monitoring programs, as there is a rising anthropogenic pressures from the nearby fishing port activities and forest conversion that causes sedimentation and threatens the coral reef health in Sempu Island, East Java. Furthermore, this extended checklist significantly enhances marine biodiversity records by filling knowledge gaps from understudied area in South Malang, thereby strengthening the data basis that is necessary for future coastal ecosystem monitoring and conservation in South Java Region.